1988
DOI: 10.1677/joe.0.1170397
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary and plasma vasopressin concentrations and fluid balance throughout the oestrous cycle of the rat

Abstract: Observations were made of fluid balance and vasopressin concentrations throughout the oestrous cycle of normally cyclic female rats housed under a 12 h light: 12 h darkness regime. Plasma vasopressin concentrations were found to increase progressively during the light period, falling again during the night on all days of the cycle except pro-oestrus. On this day, peak vasopressin concentrations of 3.32 +/- 0.8 pmol/l were seen between 10.00 and 12.00 h, with lower concentrations of 1.74 +/- 0.22 pmol/l being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 24 publications
2
52
1
1
Order By: Relevance
“…Food and water intake decrease during pro-estrous and estrous. Also, urinary output and urinary sodium excretion are decreased in estrous compared to diestrus (Forsling & Peysner 1988). It is known that physiological concentrations of estrogen stimulate the release of OT by the dendrites of magnocellular neurones in the SON (Wang et al 1995), and studies in our laboratory have shown that the secretion of OT varies during the estrous cycle, increasing during pro-estrous and the morning of estrous (Caligioni & Franci 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Food and water intake decrease during pro-estrous and estrous. Also, urinary output and urinary sodium excretion are decreased in estrous compared to diestrus (Forsling & Peysner 1988). It is known that physiological concentrations of estrogen stimulate the release of OT by the dendrites of magnocellular neurones in the SON (Wang et al 1995), and studies in our laboratory have shown that the secretion of OT varies during the estrous cycle, increasing during pro-estrous and the morning of estrous (Caligioni & Franci 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Inter-and intra-assay coefficients of variation were 8.1% (n = 20) and 8.3% (n = 20), respectively. AVP was extracted as described elsewhere [13] using the DSL-1800 Arginine Vasopressin Radioimmunoassay kit from Diagnostic Systems Laboratories, Webster, Texas, USA. Vasopressin was extracted from plasma using Sep Pak C18 cartridges (Millipore Water Associates, Harrow, Middlesex, UK).…”
Section: Plasma Avp and Aldosterone Measurementsmentioning
confidence: 99%
“…The lower limit of detection for the assay was 1·6 pmol/l, with intraand inter-assay variations of 4·1% (n=10) and 9·0% (n=10) respectively for 10 pmol/l. Vasopressin was determined as described by Forsling & Peysner (1988) using the First International Standard for vasopressin (77/501). The lower limit of detection for the assay was 0·12 0·02 pmol/l, with intra-and inter-assay variations of 7·7% (n=23) and 11·9% (n=10) respectively for 2·5 pmol/l.…”
Section: Radioimmunoassay Of Oxytocin and Vasopressinmentioning
confidence: 99%